Efektivitas Strategi Komunikasi Pemasaran Universitas Budi Luhur Dalam Penerimaan Mahasiswa Baru 2019 - Rismiatun Rismiatun (Jurnal Komunikasi, 2020)
AbstractAlong with the times and increasing education, especially tertiary education. All private universities offer the same thing to prospective students. Every private university competes to be able to gain trust and convince prospective students to register at the relevant university. Every college has a marketing department that has a communication strategy to be able to achieve its goals, so not only the marketing function must be carried out, but also the Public Relations (PR) function. Or we are familiar with Humas (Public Relations). This means that there is an element of marketing communication carried out by the PR function within it. Marketing communication is an important aspect in marketing missions and determines marketing success. This study aims to describe the effectiveness of the implementation of the marketing communication strategy of Budi Luhur University in the admission of new students. This research uses the postpositivism paradigm. This paradigm is to get in-depth data, a data that contains meaning. The method used in this research is descriptive qualitative, with a qualitative approach. Researchers describe and implement existing data in the field. Marketing communication strategies used in the form of school visits, events, sponsorships, blazz sms, e-marketing. From the planning, implementation of program monitoring and evaluation, found obstacles in its implementation but these obstacles can be overcome with a monitoring program, but judging by the comparison of students, the results achieved this year show this strategy is effective. Keywords: Effectiveness, Strategy, Marketing Communication